Answer: 13
Step-by-step explanation: i googled it
Answer:
-1.
Step-by-step explanation:
(tanx- secx) (tanx+ secx).
= tan^2 x + tanx sec x- tanx sec x - sec^2x
= tan^2 x - sec^2 x.
But sec^2 x = 1 + tan^2 x
so tan^2 x - sec^2 x = -1
Answer:
w <u>> </u> -6
Step-by-step explanation:
divide each term n 2x <u>> </u> -12 by 2 then simplify
Answer:
x=148
Step-by-step explanation:
First, find the missing angle by subtracting 100+48 from 180 (all of the angles in a triangle add up to 180). Then, subtract that from 180 (the angles are a linear pair, so they are supplementry, so they add up to 180) x+32=180.
x=148.
(お役に立てれば!)